1980
DOI: 10.1902/jop.1980.51.12.686
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Gingival Recession Treated by Coronally Repositioned Flap Technique

Abstract: Thirty-four areas of gingival recession in ten patients were treated by a coronally repositioned flap procedure. All but four of these areas had received a free gingiva graft previously. The postoperative evaluations of the wound healing were made at 2 weeks and at 1, 2, 4, 6 and 12 months after the final surgery. In most cases the amount of gingival recession was reduced with the average tissue gain being 1.82 mm. The gingival sulcus depth was unaffected by the procedure. Several cases showed total root cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 6 publications
2
33
0
1
Order By: Relevance
“…The present results agree with those previously reported in the literature 19,20,26,28,30,40,45,46 which demonstrate the effectiveness of both treatment approaches and show that predictable and esthetic root coverage of marginal tissue recession defects is attainable. Although statistical differences have been found, they may not be considered clinically significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present results agree with those previously reported in the literature 19,20,26,28,30,40,45,46 which demonstrate the effectiveness of both treatment approaches and show that predictable and esthetic root coverage of marginal tissue recession defects is attainable. Although statistical differences have been found, they may not be considered clinically significant.…”
Section: Discussionsupporting
confidence: 93%
“…The coronally positioned flap (CPF) technique was shown to be a predictable method for recession coverage with apparently satisfactory esthetic results and is a relatively easy procedure for the patient and clinician 19,25‐28 . According to some authors, the coronally positioned flap is the most esthetically effective mucogingival procedure for correcting localized gingival recessions 29 .…”
mentioning
confidence: 99%
“…Recession coverage by coronally advanced flap procedure does not result in pocket formation but rather tissue attachment on the previously exposed root surface. 3,25,26,[31][32][33][34][35] In the present study, PD slightly increased between the 6-month and final evaluation in both groups. Thus VRD did not decrease through PD increase.…”
Section: Discussionmentioning
confidence: 62%
“…Numerous longitudinal human studies have been presented to support the efficacy and predictability of different surgical techniques that have been proposed to address this issue. 1 The proposals can be summarized as follows: palatal masticatory mucosa grafted onto the recession area (EFGG); 2-17 only a layer of connective tissue grafted onto the recession area (CTG); 10,12,15, use of the gingiva from adjacent teeth as a rotated and/or sliding pedicle flap to cover the exposed root surface (LPF); 8,44-52 moving the residual gingiva at the recession site in a coronal direction (CAF); 26,53-63 coronal positioning of previously grafted tissue (EFGG + CAF); 14,46,[64][65][66][67][68][69][70] and use of resorbable and non-resorbable membranes according to the principles of guided tissue regeneration (GTR). 28,29,33,34,37,38,[40][41][42]58,62, A careful review made it possible to summarize the descriptive statistics reported in the published clinical studies on root coverage and to compute the missing statistics from the published data whenever possible.…”
mentioning
confidence: 99%